Phosalone Toxicity on Liver and Pancreas: Role of Vitamins E and C - Demirin, Hilmi; Gokalp, Osman; Kaya, Ertugrul; Buyukvanli, Bora; Cesur, Gokhan; Ozkan, Aybars; Kaya, Murat (Asian Journal of Chemistry, 2012)
Phosalone (6-chloro-3-[diethoxyphosphinothioylsulfanylmethyl]-1,3-benzoxazol-2-one) is one of the most commonly used organophosphorus pesticides in the pest control of crops. Subchronic phosalone exposure was evaluated for its effects on the serum activities of some enzymes concerning hepatic and pancreatic damage including aspartate aminotransferase (AST), alanine aminotransferase (ALT), glutamyltransferase (GGT), lactate dehydrogenase (LDH), alkaline phosphatase (ALP), cholinesterase (ChE); and finally protective effects of combination of vitamins E and C in 24 wistar-albino rats. Experimental groups were as follows: control group (n = 8); a group treated with 120 mg/kg body weight phosalone (P group, n = 8); and a group treated with 120 mg/kg body weight phosalone + vitamin E + vitamin C (P+V group, n = 8). The P and P+V groups were treated orally with phosalone on 5 days a week for 4 weeks. The serum activities of the above mentioned enzymes were analyzed. In the samples, phosalone significantly increased the activities of ALT, LDH and decreased ChE (p < 0.05). However no significant change was detected for the remainder enzymes (p > 0.05). In the P+V group, ALT and LDH activities were significantly increased and ChE decreased (p < 0.05). It is concluded that subchronic phosalone causes rat liver damage to an extent, which is somewhat reflected on the liver enzymes. Furthermore, a combination of vitamins E and C can reduce the toxic effects of phosalone on liver tissue of rats.